Blades of glory - Speck, Will.; Gordon, Josh.; Ferrell, Will, 1967-; Heder, Jon, 1978-; Arnett, Will.; Poehler, Amy, 1971-; Fichtner, William; Malco, Romany; Fischer, Jenna, 1974-; Nelson, Craig T.; Dreamworks Pictures; Red Hour Films; et al. (Universal City, CA : DreamWorks Home Entertainment, 2007)
Bitter ivals Chazz Michael Michaels and Jimmy MacElroy brawl on the podium after tying for gold at the world championship. Banned for life from men's single skating competition, the arch-rivals find a loophole that allows them to skate again as a pair.
Originally produced as a motion picture in 2007.
Special features: Return to glory: the making of "Blades;" Celebrities on thin ice; Cooler than ice: the super-sexy costumes of skating; Arnett & Poehler: a family affair; 20 questions with Scott Hamilton; Hector: portrait of a psychophan; deleted scenes; music video "Blades of Glory: by Bo Rice; gag reel; alternate takes.
Director of photography, Stefan Czapsky ; edited by Richard Pearson ; music by Theodore Shapiro.
Will Ferrell, Jon Heder, Will Arnett, Amy Poehler, William Fichtner, Jenna Fischer, Romany Malco, Craig T. Nelson.
MPAA rating: PG-13; for crude and sexual humor, language, a comic violent image, and some drug references.
DVD; region 1; Dolby Digital 5.1 surround.
Keywords: Figure skaters -- Drama; Figure skating -- Drama; Skating -- Tournaments -- Drama; Sports rivalries -- Drama; Figure skating. -- Fiction; Skating competition. -- Fiction; Figure skaters; Figure skating; Skating -- Tournaments; Sports rivalries; Comedy films; Video recordings for the hearing impaired; Feature films; Humorous fiction; Drama